Inverting the paradox of excellence : how companies use variations for business excellence and how enterprise variations are enabled by SAP - Kale, Vivek (CRC Press, 2015)
Drawing lessons from one of the best models of success, the evolutionary model, this book explains why an organization must pro-actively seek out changes or variations on a continuous basis for ensuring excellence by testing out a continuum of opportunities and advantages. It introduces the patterns and anti-patterns of excellence and includes detailed case studies based on different dimensions of variations, including shared values variations, structure variations, and staff variations. It presents these case studies through the prism of the "variations" idea to help visualize the difference of the "case history" approach presented here. The case studies illustrate the different dimensions of business variations available to help an organization in its quest towards achieving and sustaining excellence. This resource takes inspiration from the most proven model of success: evolution by natural selection. --